"Just working in a team was a great experience…" – Student perspectives on the learning experiences of an interprofessional education program. Issue 4 (July 2013) - Mellor, Rebecca; Cottrell, Neil; Moran, Monica
Abstract : Interprofessional education (IPE) programs aim to improve collaboration between health- and social-care professionals and to optimize clinical outcomes. Such programs are complex to design, and evaluation of effectiveness is difficult. Combining qualitative and quantitative data may provide greater understanding of how a program affects participants and what aspects are influential on attitudes and behavior. This qualitative study used semi-structured interviews and interpretative phenomenological analysis to explore undergraduate student perspectives on what attributes of a 4-week IPE program they considered contributed to a successful learning experience. Due to the fact that the students were not formally assessed, the realistic context of the activities and the quality of the facilitators created an environment where the students felt empowered to interact freely without fear of reproach. Learning the roles of other professions and their contribution to a healthcare team broadened the students' perspectives on healthcare and increased their sense of self-worth and pride in their professions. In addition, being able to identify the relevance of the learning experience to their future practice motivated the students. This information can be used to create optimal learning environments for facilitating the development of successful future healthcare teams.